Total design of polymer composite automotive bumper fascia - Suddin, Mohd Nizam; Salit, Mohd Sapuan; Ismail, Napsiah; Maleque, Md. Abdul; Zainuddin, Syams (Suranaree University of Technology, 2005)
An automobile bumper fascia is a component, which contributes to vehicle crashworthiness during front or rear collisions. In the past, the fascia was made of plastic materials. The weight reduction in the bumper fascia without sacrificing the safety of the car was extensively studied. In this paper, the bumper fascia made of polymeric based composite material was designed with solid modelling software. The polymeric based composite material was selected because of low weight, high specific stiffness, high specific strength, high-energy absorption and easy to produce in complex shapes. Four conceptual designs of a bumper fascia were developed with a 3-D solid model. To decide the final design of bumper fascia, the matrix evaluation method was used. The weight of the bumper fascia was obtained through weight analysis that had been carried out using Pro/Engineer software. The fascia was successfully designed with less weight compared to the current fascia